Dye-sensitized solar cells for efficient solar and artificial light conversion - Hora, Carolina (2019)
Progress in dye-sensitized solar cells (DSSCs) has been benchmarked with N719 dye-based devices. However, power conversion efficiency (PCE) improvements performed in low-energy-performing devices cannot be extrapolated to high-performing ones. This points to the need for using a high PCE reference DSSC device, which preferably should be possible for preparation using readily available commercial reactants and parts. This study reports an optimized DSSC prepared with commercial reactants, displaying a PCE of up to 9.84% under simulated solar light and of 28.7% under artificial room light. The efficient light harvesting in the photoanode and electron recombination suppression in the photoanode/electrolyte interface were systematically optimized; the thickness and light-scattering ability of the photoanode mesoporous layers were tuned to maximize light harvesting and minimize the recombination losses. Electron back recombination with electrolyte was minimized using a TiO2 blocking layer and treating the mesoporous layer of TiO2 with TiCl4. Finally, despite the use of a light-scattering TiO2 coating over the mesoporous layer, the use of a light reflection layer applied to the back of the devices proved to improve the PCE further.